IJN-UTM Cardiovascular Engineering Centre / Muhammad Yusuf Zulhasny - Zulhasny, Muhammad Yusuf (Faculty of Business and Management, 2023)
An internship during college studies can help to enhance quality of higher education and to improve skills and competencies amongst students. It assists students in bridging the knowledge gap between academic theory and workplace application. On the other hand, internships also assist students in achieving higher professional capabilities and proficiency in their chosen fields, enabling them to perform to their fullest potential in their future employment. Through internships, students can gain important work experience that will improve their employability after graduation, indirectly to offer students a chance to apply their academic knowledge to real-world situations. IJN-UTM Cardiovascular Engineering Center was selected by Muhammad Yusuf bin Zulhasny to fulfil his internship requirements from 12 March until 24 August 2023. On the first part of the report, he should insert his profile which is the resume with current information. This includes his name, home address, education history, work history and even his achievements. Followed by the company that he chooses to fulfil his internship requirements. He will describe about the company including the name, logo, location, operation hour, vision, mission, objectives, goals, background of establishment, organizational structure and product or services offered. Next, is the main part of the report that includes the training’s reflection. This is the part where he will write about the industrial training experience. For example, the duration of his internship, specific his department that was assigned to, the roles or responsibilities that was assigned, and the benefits that he received and gained throughout his internship. Furthermore, SWOT Analysis also will be described by him. This includes the strength, weakness, opportunities and threat to the department he chooses. Lastly, he will give his final thoughts and recommendations on his 24-week internship in the department. With that, he has gained many valuable experiences in the department throughout the internship with IJN-UTM Cardiovascular Engineering Center, which allowed his to put his studies at UiTM into practice